3D‐Printing: 3D‐Printed Autonomous Sensory Composites (Adv. Mater. Technol. 3/2017). Issue 3 (March 2017) - Sundaram, Subramanian; Jiang, Ziwen; Sitthi‐Amorn, Pitchaya; Kim, David S.; Baldo, Marc A.; Matusik, Wojciech
Abstract : Sensorimotor pathways in nature integrate multiple materials and functions in three dimensions. One such pathway in golden tortoise beetles enables them to modulate their color in response to external disturbances. Inspired by this, Subramanian Sundaram and co‐workers demonstrate in article number 1600257 a fully 3D‐printed composite operating at 1.5 V that can sense strain, electrically amplify the signal, and respond optically.